PENINGKATAN KINERJA PELAYANAN PUBLIK KELURAHAN MELALUI PENERAPAN BALANCED SCORECARD TERINTEGRASI - Uning Heri Gagarin; Hendri Mayanta; Evlin Anariska Sebayang (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This Community Service activity aims to improve the performance of urban village public services through the implementation of an integrated Balanced Scorecard (BSC) as a performance management system that translates the vision and mission into strategic objectives, key performance indicators (KPIs), service targets, and periodic monitoring and evaluation mechanisms. Problems faced by partners include variations in service times, service standards that are not yet uniform among officers, inconsistent process documentation, and performance reporting that is not yet indicator-based. Interventions are carried out through measuring service baselines, developing strategy maps, formulating KPIs and SLAs, preparing SOPs and file checklists, developing performance dashboards (Excel/Google Sheet), and assisting with monthly performance review meetings. The expected results are reduced waiting times and service completion times, increased SOP compliance, increased citizen satisfaction, and the formation of a culture of continuous improvement in the urban village.